ALEGORI DALAM LIRIK LAGU BERMAKNA RELIGIUSITAS GUNA MENINGKATKAN PEMAHAMAN - Dwi Faradylla Nur Khasanah; Rima Listiawati; Khofifah Nur Khasanah; Titik Sudiatmi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2024)
The use of language styles in a literary work, especially songs, aims to increase the aesthetic effect or beauty so that it gives the impression of attracting someone's attention to reading or listening. This paper aims to describe the meaning of religious songs through the use of allegorical language. Qualitative descriptive methods were used as this research method. The three song objects used in this study were taken through YouTube media in 2024, including a song by Saujana titled “Sepohon Kayu”, Chrisye's song “Ketika Tangan dan Kaki Berkata”, and a song by Fatin Shidqia titled “Oh Tuhan”. This data was used to investigate the meaning of religiosity in song lyrics. Researchers use documentation techniques in collecting research materials which are of course valid. Apart from that, researchers also use listening techniques, recording techniques, and data analysis techniques. After research, this study shows the use of allegorical language styles in these songs and proves an understanding of the meaning of religiosity in them. Through this research, it can provide a better understanding and become a powerful tool for conveying spiritual or religious messages in songs that have a meaning of religiosity.